Relevansi Pemikiran Pendidikan KH. Imam Zarkasyi Dalam Pembentukan Intrapersonal Intelegensi - Adawiyah, Robiatul; Rahmawati, Ryan Eka; Salik, Mohamad (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
This article discusses about the relevance of KH Imam Zarkasi thoughts of education in developing intrapersonal intelligence. It is a kind of library research using descriptive-qualitative method. The resutt of this research shows that KH. Imam Zarkasi`s thoughts are still very relevant to be implemented in developing students` intrapersonal intelligence. Among of his thoughts are; 1) developing intrapersonal intelligence can be through two ways; intentionally, that is through education in formal institutions, and unintentionally that is through interaction with the surrounding community and the nature. 2) The method of learning to develop intrapersonal intelligence is through individual training; by entrusting children to carry out their own duties with full responsibility, giving children the opportunity to make their own decisions and be responsible for their decisions, and other similar activities. These thoughts have been applied by KH Imam Zarkasi through the institution he developed, namely Pondok Pesantren Gontor. Among of his renewal efforts are; The implementation learning using classical system, the use of learning methods that provide opportunities for children to develop their thinking power critically, independently and responsibly, and provide extracurricular activities as a forum for students to develop themselves. Education Thoughts, KH. Imam Zarkasyi, Intrapersonal Intelligence